PENGARUH PIUTANG AL-BAI’ DAN INVESTASI SYIRKAH TERHADAP KINERJA KEUANGAN BANK SYARIAH - Ahmad Agit Patrianto; Anik Malikah; Moh. Amin (e_Jurnal Ilmiah Riset Akuntansi, 2020)
This study aims to determine the effect of trade receivable and profit sharing investment on Financial Performance that is measured using Return On Assets (ROA) in Islamic Banks. The population in this study is a Sharia Bank registered on the Indonesian Stock Exchange (BEI) during the 2015-2018 period, populations there were 8 Sharia Banks that had criteria for the study sample. The data used in this study is the annual financial statements published on the official website of the Sharia Bank. The analysis technique used is multiple linear regression analysis by SPSS software. This analysis is to determine the influence of trade receivable and profit sharing investment. The results of this study indicate that trade receivable affect financial performance positively and profit sharing investment affect the Financial Performance negatively.Keywords: Receivable, investment, Financial Performance, and Islamic Banks